Injury History in the Collegiate Equestrian Athlete: Part I: Mechanism of Injury, Demographic Data and Spinal Injury - Michael L. Pilato; Timothy Henry; Drussila Malavase (Bowling Green State University, 2017)
Purpose: Equestrian sports are known to have a high risk and rate of injury. While there is injury data available on acute injuries in the equestrian population, it is of a general nature. Within that data appears to be a lack of information on the collegiate equestrian athlete. Thus, the purpose of the current study and this analysis is to describe the demographics and incidence of spinal injuries found in intercollegiate equestrian athlete. Method: A survey was developed with input from each author and implemented in Mach forms. It was sent to 43 equestrian coaches in the Eastern United States who passed it on to their athletes. We estimated 753 athletes would have access to the survey and had a total of 73 respondents. Descriptive statistics were calculated for total number of injuries for each injury category. Results: Demographic information, conditioning activity, riding style, pain medication use, total responses (injuries) per body area and injuries to the spine and pelvis are detailed in tables 1-6. Of interesting note is only 73% of respondents reported having access to or utilizing the schools athletic program as part of their participation on the schools equestrian team. Conclusions and Recommendations: The current study is amongst the first, if not the first, to report specifically on injury patterns and frequency in US collegiate equestrian athletes. There were several findings that from a sports medicine and athletic perspective are concerning. The lack of overall knowledge and research about the equestrian athlete would appear to put it in the same position as cheerleading was 20 years ago. Significantly more sport specific research is needed to improve the health and safety of the athletes.